Immunotherapy of renal cell cancer – new targets and new strategies - Wysocki, Piotr J.; Żołnierek, Jakub (Contemporary Oncology/Współczesna Onkologia, 2008)
Various immunotherapeutic approaches for the treatment of renal cell carcinoma (RCC) have been developed for >90 years. However, the majority of them were clinically ineffective. Objective clinical effects have been seen only in the case of systemic administration of recom-binant cytokines – IFN-alpha and IL-2. With the advent of molecularly targeted biological therapies, which turned out to be significantly effective in the treatment of metastatic RCC, to many oncologists immunotherapy may seem to be moving into the periphery of RCC treatment strategies. However, various novel, sophisticated immunotherapeutic appro-aches for the treatment of RCC are still being developed. The development of active and passive specific immu-notherapeutic approaches, along with the possibility to \'switch off\' particular immunosuppressive mecha-nisms (e.g. elimination of regulatory T cells, blockage of cytotoxic T lymphocyte antigen-4 signalling), have paved the way for future trials of new immunotherapies of RCC. However, the new studies will have to enrol optimally selected patients (nephrectomized, with non-massive metastases and good performance status) and will use tumour response criteria that are specifically optimized for clinical trials of immunotherapy.